Myocardial scarring by delayed enhancement cardiovascular magnetic resonance in thalassaemia major. Issue 20 (1st June 2009) - Pepe, A; Positano, V; Capra, M; Maggio, A; Pinto, C L; Spasiano, A; Forni, G; Derchi, G; Favilli, B; Rossi, G; Cracolici, E; Midiri, M; et al.
Abstract : Background: Cardiovascular magnetic resonance (CMR) by delayed enhancement (DE) enables visualisation of myocardial scarring, but no dedicated studies are available in thalassaemia major. Objective: To investigate the prevalence, extent, clinical and instrumental correlates of myocardial fibrosis or necrosis by DE CMR in patients with thalassaemia major. Patients: 115 Patients with thalassaemia major consecutively examined at an MRI laboratory. Methods: DE images were acquired to quantify myocardial scarring. Myocardial iron overload was determined by multislice multiecho T2*. Cine images were obtained to evaluate biventricular function. Results: DE areas were present in 28/115 patients (24%). The mean (SD) extent of DE was 3.9 (2.4)%. In 26 patients the location of fibrosis was not specific and patchy distribution was prevalent. Two patients showed transmural DE following coronary distribution. The DE group was significantly older than the no-DE group (31 (7.7) years vs 26 (7.7) years, p = 0.004). No significant relation with heart T2* values and biventricular function was found. A significant correlation was found between the presence of DE and changes in ECG (ECG abnormal in the DE group 22/28 patients and in the no-DE group 30/87 patients; χ 2  = 14.9; p<0.001). Conclusions: In patients with thalassaemia the significant presence of myocardial fibrosis/necrosis seems to be a time-dependent process correlating with cardiovascular risk factors and cardiac complications. Levels of HCV antibodies are significantly higher in the serum of patients with thalassaemia with myocardial fibrosis/necrosis. ECG changes showed a good accuracy in predicting myocardial scarring.